Pengaruh Partisipasi Anggaran dan Komitmen Organisasi terhadap Kinerja Manajerial pada Perhotelan di Kota Padang - Fardhila Amani; Halmawati Halmawati (Universitas Negeri Padang, 2022)
This study aims to examine the effect of budget participation and organizational commitment on managerial performance. Type of this research is a quantitative research. The population in this study 37 hotels in the city of Padang. The sampling technique used the purposive sampling. This study uses subject data and the sources of the data of this research is the primary data. This study used a questionnaire survey method. The data analysis technique uses in this study are multiple linear regression analysis, with managerial performance as the dependent variable, budget participation and organizational commitment as the independent variable. The results of this study indicate that budget participation and organizational commitment has positive significant influence of managerial performance.